Engaging primary care providers in a mobile health strategy to support lifestyle change and blood pressure management. (December 2021) - Nau, Tracy; Owen, Alice; Mazza, Danielle; Smith, Ben J
Objective: The delivery of lifestyle advice concerning diet and physical activity has been found to be suboptimal in primary care settings, including for patients who require this for clinical management. This pilot study aimed to evaluate the acceptability and feasibility of integrating a mobile health intervention into primary care to support patients with improving lifestyle behaviours for high blood pressure. Methods: Thirty-one patients aged 40–70 years were recruited by seven general practitioners to trial a 6-month mobile health intervention that included videos, web-based education and text message reminders. Semi-structured interviews with general practitioners and patients explored intervention feasibility and acceptability. Web analytics were used to measure intervention use, and pre- and post-questionnaires measured patient ratings of content and behaviour changes. Results: General practitioners and patients perceived the intervention to be an acceptable tool for supporting high blood pressure management. However, general practitioners reported recruitment challenges and patient engagement was limited for the web and video components. Questionnaires revealed no significant changes in behaviours, although the program was generally regarded by patients as motivating and some reported acquiring new knowledge and awareness. Patient suggestions for improvement included greater individualisation of content and opportunity for interaction with their general practitioner. Conclusions: There is scope to improve lifestyle interventions for the management of high blood pressure in the busy primary care environment using supplementary mobile health strategies. Further intervention refinement and formative evaluation is required to identify strategies that can be integrated into routine care and achieve high patient engagement.